Vacuolar invertase gene silencing in potato (Solanum tuberosum L.) improves processing quality by decreasing the frequency of sugar-end defects. - Xiaobiao Zhu (Public Library of Science (PLoS), 2014)
Sugar-end defect is a tuber quality disorder and persistent problem for the French fry processing industry that causes unacceptable darkening of one end of French fries. This defect appears when environmental stress during tuber growth increases post-harvest vacuolar acid invertase activity at one end of the tuber. Reducing sugars produced by invertase form dark-colored Maillard reaction products during frying. Acrylamide is another Maillard reaction product formed from reducing sugars and acrylamide consumption has raised health concerns worldwide. Vacuolar invertase gene (VInv) expression was suppressed in cultivars Russet Burbank and Ranger Russet using RNA interference to determine if this approach could control sugar-end defect formation. Acid invertase activity and reducing sugar content decreased at both ends of tubers. Sugar-end defects and acrylamide in fried potato strips were strongly reduced in multiple transgenic potato lines. Thus vacuolar invertase silencing can minimize a long-standing French fry quality problem while providing consumers with attractive products that reduce health concerns related to dietary acrylamide.